PENERAPAN MODEL LEARNING CYCLE 5E UNTUK MENINGKATKAN KETERAMPILAN PROSES SAINS MATERI KALOR DAN PERPINDAHANNYA - Dita Dwi Anggreyni; Tomo Djudin; Diah Mahmuda (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractThis research was purposed to find out the effectiveness of the implementation of learning cycle 5E in improving science process skills of the students in heat and displacement . Pre-Experimental design with one group pre-test and post-test was used in this research. The population is all the students of class VII SMP Swasta Pancasila. Using simple random sampling the sample of this research was VIIA that have 20 studentes. This research instrument used test that have 6 essay questions. The average of the students KPS test result before the implementation of learning cycle 5E was 20,90, where as the students KPS test result after the implementation of learning cycle 5E was at 36,20. T-test was conducted to show an increase after applying learning cycle 5E. Learning cycle 5E models increased students’s KPS on heat and displacement with gain score as of 0.57 in the medium category. In conclusion, learning cycle 5E is applicable to be used as learning method to improve students’s KPS. Keyword: heat and displacement, learning cycle 5E, science process skills.